Crescimento, demanda agregada e distribuição pessoal da renda no Brasil: 1996 a 2015 - Almeida, Alex; Alencar, Douglas (Brazilian Keynesian Review, 2022)
Considering the Post-Keynesian economic growth literature, the demand regimes emerge as an important factor. The demand regimes explore the impact of changes in the functional income distribution on economic growth. In the case of redistribution of income from profits to wages promotes economic growth, it’s said the economy is wage-led, in the opposite case, the economy is profit-led. This research estimates a Vector Autoregression (VAR) from 1996 to 2015 to investigate if the Brazilian demand regime can be considered wage-led or profit-led. Furthermore, it is included the personal income distribution with the purpose to avoid a possible omitted variable bias arising for ignoring the effects that a changing on that distribution can has over demand regimes.